Preception of fourth year MBBS students regarding online learning during Covid-19 pandemic - Minahil Iram, Seema Daud, Maha Anjum, Muhammad Ahsan Zia, Mubeen Ahmad Danial, Muhammad Abubakar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the perception of fourth year MBBS students regarding online learning during Covid 19 pandemic. Study Design: Cross sectional survey. Setting: Department of Community Medicine, Lahore Medical and Dental College, Lahore. Duration of study: Four months, from April to July, 2022. Study population: All students registered in fourth year MBBS. Methodology: A structured questionnaire was used to collect data from 154 study participants. It consisting of two sections. The first part consisted of background information of study participants. The second portion assessed the perception of students regarding online education during Covid 19.The data was recorded and analyzed using SPSS version 21. Data were described in the form of frequencies and percentages and presented as tables. Results: Study participants included 51% females, 57%-day scholars and 83% who had done FSc. Around 62% did not find online learning effective, 73% had communication difficulties, 75% liked self-directed approach of online learning but 74% thought that it was difficult to collaborate with each other, 71% found time management easy, though it was difficult to ask questions and receiving answers (59%). Around 78% of students perceived lack of satisfaction compared with class room learning, 66% preferred face to face learning and 73% found online education less comprehensible than class room activities. Among students, 53% recognised online learning as enjoyable and 34% wanted it to be done regularly, as 32%students never experienced any difficulty during online sessions. The main issues faced in online activities were absence of internet connection (85%), poor computer skills (73%), electricity breakdown (85%) and lack of concentration (80%). Practical implication: The present study highlighted that majority of fourth year MBBS students preferred classroom learning in comparison with online sessions. In light of pandemic, online education has proven valuable in managing sudden crisis, which is why it was important to understand the student perception regarding online education during covid-19 at Lahore Medical and Dental College, Lahore. Conclusion: Compared with males, higher number of females complained of lack of internet access and having poor computer skills. Seminars and regular training must be undertaken by medical colleges for their staff and students to inculcate interest and highlight the importance of online education as one of the tools for learning. Online education must be made more interactive and student cantered to create interest and improve student concentration. Keywords: Perceptions, online learning, MBBS students, Covid-19 pandemic, face to face education, communication barriers,